Functional constipation and posture in defecation - Fahrul Azmi Tanjung; Supriatmo Supriatmo; Atan Baas Sinuhaji; Hakimi Hakimi (Paediatrica Indonesiana, 2013)
Background Functional constipation is often a consequence ofhabitual bowel elimination while sitting on common toilet seats.A considerable proportion of the population with n ormal bowelmovement frequency has difficulty emptying their bowels. Theprincipal cause of this problem may be the obstructive nature ofthe rectoanal angle and its relationship to the posture normallyused in defecation.Objective To assess the relationship between functional constipationwith the posture (sitting vs squatting) during defecationin children.Methods We conducted a cross-sectional study in November2010. Participants aged 12- 15 years were selected consecutivelyfrom a junior high school in Medan . Parents and children filledquestionnaires and were interviewed. Functional constipation wasassessed based on the Rome III criteria.Results Sixty-five students enrolled in the study. There was nostatistically significant diffe rences in subjects' characteristics.T here was a significant correlation between functional constipationwith posture during defecation in children (RR= 0.06, 95%CI0.02 to 0.25; P=0.0001). Functional constipation was more likelyoccured in children with sitting (12/20) th an squatting posture(4/45) during defecation.Conclusion We found th at posture in defecation is correlatedto functional con stipation in children.